2022
DOI: 10.1242/dev.200179
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell genomics revolutionizes plant development studies across scales

Abstract: Understanding the development of tissues, organs and entire organisms through the lens of single-cell genomics has revolutionized developmental biology. Although single-cell transcriptomics has been pioneered in animal systems, from an experimental perspective, plant development holds some distinct advantages: cells do not migrate in relation to one another, and new organ formation (of leaves, roots, flowers, etc.) continues post-embryonically from persistent stem cell populations known as meristems. For a tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
3
1
0
Order By: Relevance
“…Comparison of marker genes defined using spatial transcriptomics in this study to orthologs in Arabidopsis and rice revealed that while some had similar a same expression pattern on a tissue basis, the majority did not. This is similar to studies using scRNA-seq showing the expression of some genes in meristems (root or shoot apical meristem) were conserved and, in general, patterns are conserved across species when similar functions and structures are required ( 9 ). Approximately 65% of genes in plant genomes are duplicates and most crops are polyploid, consequently for many important agronomic traits such as seed size and disease resistance the spatial expression pattern of genes arising from subfunctionalisation and subneofunctionalisation is an important mechanism for retaining duplicates ( 123 ).…”
Section: Discussionsupporting
confidence: 84%
“…Comparison of marker genes defined using spatial transcriptomics in this study to orthologs in Arabidopsis and rice revealed that while some had similar a same expression pattern on a tissue basis, the majority did not. This is similar to studies using scRNA-seq showing the expression of some genes in meristems (root or shoot apical meristem) were conserved and, in general, patterns are conserved across species when similar functions and structures are required ( 9 ). Approximately 65% of genes in plant genomes are duplicates and most crops are polyploid, consequently for many important agronomic traits such as seed size and disease resistance the spatial expression pattern of genes arising from subfunctionalisation and subneofunctionalisation is an important mechanism for retaining duplicates ( 123 ).…”
Section: Discussionsupporting
confidence: 84%
“…Comparison of marker genes defined using spatial transcriptomics in this study to orthologs in Arabidopsis revealed that while some Arabidopsis genes had similar a same expression pattern on a tissue basis, the majority did not. This is similar to studies using scRNA-seq showing he expression of some genes in meristems (root or shoot apical meristem) were conserved, and, in general, patterns are conserved across species when similar functions and structures are required 9 . Approximately 65% of genes in plant genomes are duplicates and most crops are polyploid, consequently for many important agronomic traits such as seed size and disease resistance the spatial expression pattern of genes arising from subfunctionalisation and subneofunctionalisation is an important mechanism for retaining duplicates 89 .…”
Section: Discussionsupporting
confidence: 84%
“…The first scRNA-seq studies in plants were applied to root tissues [3][4][5] because of their spatially defined developmental profile along the longitudinal axis and the relative ease of isolating individual cells. scRNA transcriptomes are also emerging for other organs, showing that this approach can be successfully applied to a variety of tissues [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…The study allowed to obtain spatially resolved cellular map for barley germination and identifies specific functional genomics targets to characterize better cellular processes during germination. Results of Peirats-Llobet et al [74] study extends previous attempts of using single-cell RNA-seq for deciphering of root and other organ transcriptomes [55,75], as time-series spatial transcriptomic analysis of transcriptome allows far more complex output from all cell types in the investigated tissue/ organ with preserved information on their spatial location. Visium methodology allowed also for detection of 83-90% transcripts reported from the previous, tissue-specific studies [76], however only a portion of seed tissue was subjected to RNA-seq.…”
Section: Seed Transcriptomessupporting
confidence: 61%